“He blet nachui was in a shop”: Swearing Practices and Attitudes to Swearing among Vilnius Adolescents - Čekuolytė, Aurelija (Taikomoji kalbotyra, 2014)
The aim of this article is to analyse swearing practices of Vilnius adolescents and the identities, associated with those practices from the attitudinal and interactional perspectives. The data, which the analysis is based on, consist of the questionnaire survey, completed by 79 adolescents, and two extracts of adolescents’ spontaneous conversations. In the questionnaire, adolescents were asked to evaluate their peer who uses a huge amount of Russian swearwords blet and nachui and their peer who uses the English swearword fuck, i.e. to examine if there are differences in attitudes towards the well-established and generally regarded as very obscene Russian swearwords and the recently appeared English swearwords. Swearing in Russian in the attitudinal questionnaire study was associated with the construction of the masculine streetwise identity. However, the interactional analysis of swearing in Russian shows that Russian swearwords can be employed in the construction of a female streetwise and a masculine non-streetwise identity. The English fuck, which was considered the mild swearing among Vilnius adolescents in the questionnaire study, does not invoke any specific youth social category.